Peran Polisi Pariwisata dalam Penanggulangan Pencurian dengan Kekerasan di Kawasan Pariwisata Polres Badung - Kadek meyer Setyawan; AAA. Ngurah Tini Rusmini Gorda (Universitas Pendidikan Nasional, 2025)
This study aims to analyze the role of tourism police in addressing violent theft crimes in tourism areas within the jurisdiction of the Badung Police Resort. The research method used is a descriptive qualitative approach with data collected through interviews, observations, and documentation. The results show that tourism police play a strategic role in ensuring the safety of tourists through preventive measures such as routine patrols and awareness campaigns, as well as repressive actions in handling criminal cases. Challenges include limited personnel, tourists' low awareness of personal security, and the complexity of the vast tourism area. To optimize the role of tourism police, enhanced training, cross-sector collaboration, and the use of modern surveillance technology are required